Preoperative Narcotic Use and Inferior Outcomes After Anatomic Total Shoulder Arthroplasty: A Clinical and Radiographic Analysis. Issue 5 (1st March 2019) - Thompson, Kirk M.; Hallock, Justin D.; Smith, Richard A.; Brolin, Tyler J.; Azar, Frederick M.; Throckmorton, Thomas W.
Abstract : Introduction: Our purpose was to determine whether the chronic use of preoperative narcotics adversely affected clinical and/or radiographic outcomes. Methods: Seventy-three patients (79 shoulders) with primary total shoulder arthroplasty for osteoarthritis were evaluated clinically and radiographically at preoperative visits and postoperatively at a minimum follow-up of 2 years: 26 patients (28 shoulders) taking chronic narcotic pain medication for at least 3 months before surgery and 47 patients (51 shoulders) who were not taking narcotics preoperatively. Results: Postoperatively, significant differences were noted between the narcotic and nonnarcotic groups regarding American Shoulder and Elbow Surgeons scores and visual analog scale scores, as well as forward elevation, external rotation, and all strength measurements ( P < 0.01). The nonnarcotic group had markedly higher American Shoulder and Elbow Surgeons scores, better overall range of motion and strength, and markedly lower visual analog scale scores than the narcotic group. Conclusion: Chronic preoperative narcotic use seems to be a notable indicator of poor outcomes of anatomic total shoulder arthroplasty for glenohumeral osteoarthritis.